2020
DOI: 10.21203/rs.3.rs-42531/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of Exosomal miR-146a-5p from Cancer-Associated Fibroblasts After Androgen Deprivation Therapy Contributes to Prostate Cancer Metastasis

Abstract: Background: Androgen deprivation therapy (ADT) is the backbone of therapy for advanced prostate cancer (PCa). Despite the good initial response, castration resistance and metastatic progression will inevitably occur. Cancer-associated fibroblasts (CAFs) may be implicated in promoting metastasis of PCa after ADT. Our aim is to investigate the role and mechanism of CAF-derived exosomes involving in metastasis of PCa after ADT. Methods: PCa cells were co-cultured with exosomes derived from 10 nM dihydrotestostero… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The lipid outer membrane of Exos can protect the various encapsulated nucleic acids, proteins, lipids and other signaling molecules, enabling them to facilitate intercellular communication. Among these cargos, exosomal microRNAs (miRNAs) are believed to play an important role in the biological processes of tumor immunity [ 11 ], the inflammatory response and oxidative damage [ 12 ], apoptosis [ 13 ], and cancer metastasis [ 14 ]. Recent evidence has shown that Exos derived from MSCs (MSC-Exos) have similar biological functions to MSCs and play an important role in MSC-mediated tissue repair and regeneration [ [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…The lipid outer membrane of Exos can protect the various encapsulated nucleic acids, proteins, lipids and other signaling molecules, enabling them to facilitate intercellular communication. Among these cargos, exosomal microRNAs (miRNAs) are believed to play an important role in the biological processes of tumor immunity [ 11 ], the inflammatory response and oxidative damage [ 12 ], apoptosis [ 13 ], and cancer metastasis [ 14 ]. Recent evidence has shown that Exos derived from MSCs (MSC-Exos) have similar biological functions to MSCs and play an important role in MSC-mediated tissue repair and regeneration [ [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we considered that the effects of miR‐146a‐3p on cell viability and motility are associated with the ERK1/2 signaling pathway in PCa. Consistent with this, a comprehensive analysis of PCa reported that the EGFR/ERK1/2 pathway (Zhang et al, 2020) is controlled by miR‐146, which mediates tumor suppression. However, this study had certain limitations.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, evidence has been presented demonstrating an enrichment of miR-146a-5p in the EVs secreted by cervical cancer cells. Similarly, miR-146a-5p in EVs from cancer-associated fibroblasts can enhance EMT to accelerate prostate cancer cell metastasis [27]. In addition, it is reported that breast cancer-derived EVs carrying miR-146a contributed to the invasion and metastasis of breast cancer cells through activating cancerassociated fibroblasts [28].…”
Section: Discussionmentioning
confidence: 98%